2015
DOI: 10.1016/j.scitotenv.2015.01.059
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and determinants of urinary biomarkers of exposure to organophosphate insecticides in Puerto Rican pregnant women

Abstract: Globally, human exposures to organophosphate (OP) insecticides may pose a significant burden to the health of mothers and their developing fetuses. Unfortunately, relevant data is limited in certain areas of the world concerning sources of exposure to OP insecticides in pregnant populations. To begin to address this gap in information for Puerto Rico, we studied repeated measures of urinary concentrations of 10 OP insecticide metabolites among 54 pregnant women from the northern karst region of the island. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 31 publications
4
13
1
1
Order By: Relevance
“…Diet has been identified as the primary source of exposure in the general population (Becker et al, 2006;McKone et al, 2007). Several studies have recently investigated the influence of various foods and food groups (Fortes et al, 2013;Lewis et al, 2015;Jardim et al, 2018). When OPs and PYR enter human body, they are metabolized and then excreted in the urine, either in free form or bound to glucoronic acid or sulfates (Barr, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Diet has been identified as the primary source of exposure in the general population (Becker et al, 2006;McKone et al, 2007). Several studies have recently investigated the influence of various foods and food groups (Fortes et al, 2013;Lewis et al, 2015;Jardim et al, 2018). When OPs and PYR enter human body, they are metabolized and then excreted in the urine, either in free form or bound to glucoronic acid or sulfates (Barr, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies investigating prenatal OP pesticides exposure have observed that maternal characteristics, such as education, smoking, social economic status (SES), body mass index (BMI), and diet (especially the consumption of fruits and vegetables) are associated with DAP metabolite concentrations in urine (Lewis et al, 2015; Llop et al, 2017; Sokoloff et al, 2016; Yolton et al, 2013). This was confirmed in two pilot studies in the Netherlands, both embedded in the Generation R Study.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge only one study with a large sample size have jointly tested the different determinants of DAP metabolite concentrations to investigate what the main source of OP pesticides exposure in pregnant women is (Llop et al, 2017). In contrast, most other studies relating dietary intake and other determinants to DAP metabolite concentrations used bivariate models wherein each possible predictor was tested separately (Lewis et al, 2015; Sokoloff et al, 2016; Yolton et al, 2013). Moreover, several studies, including our pilot study, investigated only broad food group categories (e.g., fruit) (Spaan et al, 2015; Yolton et al, 2013) while few studies explored specific food items (e.g., apples) (Llop et al, 2017; Sokoloff et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Algunos estudios recientes llaman la atención sobre la falta de estudios que determinen la exposición a plaguicidas en poblaciones de riesgo como las mujeres embarazadas (3,4,5), situación que también se repite en Chile.…”
Section: Introductionunclassified